2020
DOI: 10.1108/bij-12-2018-0409
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of quality awards on the company's performance – the case of Iran's national quality awards

Abstract: PurposeThe purpose of this study is to clarify the relationship between getting quality awards by companies and their financial performance in Iran's business.Design/methodology/approachIn the first step, the relationship between awards scores and financial performance by canonical correlation analysis was examined. Then, binary and multinomial logistic regression was used to determine the degree of impact of each financial performance measure on getting quality awards. Finally, two forecasting functions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Leadership emerged clearly in EFQM2020, where it focused on strengthening the role of leadership for possible change, creating its conditions, improving it, and leading it successfully (Periañez-Cristobal et al, 2021). Leadership also emerged in the model in terms of focusing on continuous communication between working individuals and leaders on the one hand, and between leaders and stakeholders on the other hand, in order to be able to understand the needs of the organization and quickly interact with it and create added value based on sustainability (Safari et al, 2020).. The EFQM model contributed to providing a complete blueprint for organizations to improve their culture and direct them towards improvement and innovation.…”
Section: Murthy Et Al(2021amentioning
confidence: 99%
“…Leadership emerged clearly in EFQM2020, where it focused on strengthening the role of leadership for possible change, creating its conditions, improving it, and leading it successfully (Periañez-Cristobal et al, 2021). Leadership also emerged in the model in terms of focusing on continuous communication between working individuals and leaders on the one hand, and between leaders and stakeholders on the other hand, in order to be able to understand the needs of the organization and quickly interact with it and create added value based on sustainability (Safari et al, 2020).. The EFQM model contributed to providing a complete blueprint for organizations to improve their culture and direct them towards improvement and innovation.…”
Section: Murthy Et Al(2021amentioning
confidence: 99%
“…(2013) reported that the stock performance of Taiwan QA winners is not better than the average of the stock market. Insignificant market responses have been attributed by scholars to immature markets (Tuck, 2005; Zhang et al ., 2021) or unsuitable business environments for QA models (Safari et al ., 2020). Therefore, there might be a lack of consensus in the literature regarding the relationship between QA and firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only a limited number of studies discussed the contextual factors and their effects on the relationship, except for some category variables such as firm size, industry, and capital intensity (Hendricks and Singhal, 1997, 2001; Lin and Su, 2013; Zhang et al ., 2021). The results of the relationship are not all significant and positive in various economies and cultures (Lin et al ., 2013; Safari et al ., 2020; Tuck, 2005). Since China is an emerging economy and a major manufacturing country (Zhang et al ., 2021), and the importance Chinese companies have placed on quality management in recent years (Ikram et al ., 2020), as well as China's strong government control (Wen et al ., 2015), the discussion of the relationship between CQA and performance is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing business excellence models has become a critical competitive priority for organisations, but the variability in the results obtained by implementing such models and the importance of such results remain open for discussion (Gómez-López et al , 2019). Various National Quality Awards (NQA) are created to assess an organisation's current situation and identify its strengths and areas for improvement (Safari et al , 2020).…”
Section: Introductionmentioning
confidence: 99%